A Systematic Approach to Handle Reference Queries - Sharma, Sumati (DESIDOC Journal of Library & Information Technology, 2003)
The need of information service in special libraries has been outlined. It discusses various facets of reference queries and suggests a working model for handling queries in a more systematic way. It also*lists key information resources of print as well as electronic media available at Defence Science Library in the area of Defence Science and Technology. http://dx.doi.org/10.14429/dbit.19.4.3494